Design of Active Electrospun Mats with Single and Core-Shell Structures to Achieve Different Curcumin Release Kinetics - Galotto-Lopez, M; Rojas-Sepulveda, A; Lopez de Dicastillo-Bergamo, A; Garrido-Ayala, L; Velasquez, E (Elsevier Ltd, 2020)
In this work, core-shell electrospun mats based on poly (lactic acid) (PLA) and polyvinyl alcohol (PVA) were developed as novel curcumin release materials. The effect of the incorporation of cellulose nanocrystals (CNN) in the PLA shell structure on structural, thermal and curcumin release were studied. A phenomenological mass transfer model was used to correlate the experimental release kinetic data as well as the structural and thermal characterization of the electrospun mats. Curcumin distribution coefficients (KP/SA) values for core-shell electrospun PLA/PVA mats were higher than KP/SA values of uniaxial active PLA. Modelling analysis evidenced PLA/PVA coaxial structures slowed down the effective diffusion coefficients of curcumin, and this value notoriously decreased by the incorporation of CNC in the PLA shell matrix due to the tortuous path created through the PLA matrix. © 2020 Elsevier Ltd
Keywords: Coaxial electrospinning; Poly (lactic acid); Polyvinyl alcohol; Curcumin; Cellulose nanocrystals; Release kinetic